Worries across Time and Age in Germany: Bringing Together Open- and Close-Ended Questions - Julia Rohrer; Martin Bruemmer; Jürgen Schupp; Gert G. Wagner (Institute of Labor Economics (IZA), 2017)
We investigate how worries in Germany change across time and age, drawing on both closed-ended questions (which typically list a number of worry items) and open-ended questions answered in text format. We find that relevant world events influence worries. For example, worries about peace peaked in 2003, the year of the Iraq War, with a considerable number of respondents also referring to the Iraq war in their text responses. Furthermore, we found that – controlling for these historical effects – worries about various topics such as health and the general economic situation increase with age. With increasing age, respondents also became more likely to answer the open-ended question. This suggests that the age increases in worries we found are not merely a result of an age-biased choice of worry items, but instead also hold for worries self-generated by the respondents.
Keywords: C81; C83; I31; Z13; 330; life course; worries; satisfaction; German Socio-Economic Panel Study; SOEP